Influence of Economic Literacy and Digital Literacy on Economic Teacher Readiness: Mediating Role of Self-Efficacy - Chelsea Aura Brilliants; Riza Yonisa Kurniawan (Dinamika Pendidikan, 2025)
This research examines how economic literacy and digital literacy influence economic teacher readiness through self-efficacy as a mediating variable among Economic Education students from the State University of Surabaya. Using an explanatory research type and a quantitative approach, this study employs PLS-SEM methodology. The investigation gathered questionnaire responses from 106 participants, using the proportionate stratified random sampling technique. First, the result of this study stated that economic literacy does not significantly influence economic teacher readiness. Second, digital literacy and self-efficacy positively influence economic teacher readiness. Third, economic literacy and digital literacy also have a positive influence on self-efficacy. Last, while self-efficacy did not mediate the influence of economic literacy, it did mediate the influence of digital literacy on economic teacher readiness. These results suggest the necessity for alternative comprehensive approaches to improve economic literacy towards economic teacher readiness, other than through self-efficacy. Therefore, educational institutions should enhance digital literacy and self-efficacy to boost economic teacher readiness.